Advanced techniques for knowledge management and access to strategic information. Issue 2 (April 2015) - Ogiela, Lidia
Highlights In the paper was described advanced techniques for knowledge management. These techniques are designed to analyse strategic data in knowledge management. Strategic management based on cryptographic algorithms. An idea of management secret data was presented.